DISCOURSE BY/ABOUT A DRIFT CHARACTER IN THE STORY “AMOR” BY CLARICE LISPECTOR (Muitas Vozes, 2024)
Silencing, invisibility, inferiority, standardization of bodies and behaviors are words that cross and constitute the discourses that have traced the history of women, who have always been subjectivized by historically engendered truths. Truths that argue from their body, their sexuality, their way of being and living in the world. In this context, there is Ana, the female protagonist of Clarice Lispector's short story "Amor", who, at a certain moment in her story, goes through an epiphany, being adrift, that is, on the threshold of the new world that presents itself before her. Thus, this article aims to shed light on this woman, summoning, on the one hand, Foucauldian Discursive Studies, notably the concepts of discourse, subject and truth as proposed by Michel Foucault; on the other hand, and in addition, the perspective of literature outside itself, based on the discussions of Natalia Brizuela and Florencia Garramuño, in order to bring together the reflections around a transgressive body that leads us to consider the limits, means and extremes present since the endo f the 1960s, resulting in a literature called by Brizuela as "conceptual". The analysis points to other possible ways to read contemporary literature, especially writing undertaken by women.